THE MEANING OF TAKSU IN HINDU SOCIETY - Rudita, I Made; I Gusti Ngurah Sudiana; I Nyoman Alit Putrawan (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Globalization and modernization affect the lives of the Hindu community in Denpasar City, especially in the aspect of the Hindu religion. The cultural traditions of Balinese society hold many mysterious things. One of them is the conception of taksu, which is believed by many Balinese people in general, and Denpasar people in particular, to be the peak energy or spiritual power that is really needed in various aspects of socio-religious life, including Balinese artistic life. So that the taksu conception can be useful for artists (pregina) in producing quality and stunning works of art, it is important to look for the implied meaning behind the taksu conception. Based on this, it is necessary to reconstruct divine teachings (theology) through research on the meaning of taksu, especially taksu pregina (artists) in Hindu society in Denpasar City. Based on this description, this research discusses the meaning of taksu in Hindu society in Denpasar City, Hindu Theological Studies. The aim of this research is to find out, explain and analyze the meaning of taksu in Hindu society in Denpasar City. The theory used in analyzing the problem formulation in this research is symbol theory. This research uses scientific methods, literature study, observation and interviews. The meaning of taksu found in fulfilling the spiritual needs of the Hindu community in Denpasar City is: (1) the religious meaning as a symbol of all artists' activities (pregina) to build and awaken the power of taksu which is classified as a religious activity, (2) the meaning of bhakti as a symbol of all artists' activities (pregina) to build and awaken the power of taksu carried out with a sense of devotion as a form of offering to God, (3) aesthetic meaning as a symbol of all the artist's activities (pregina) to build and awaken the power of taksu is very full of aesthetic values originating from religion Hinduism (4) means respecting time as a symbol that time is a very valuable thing, a blessing and gift from God given to every human being. , and (5) the meaning of work professionalism as a symbol for humans to work in their profession (gina) in accordance with the talents (guna) they have had since birth.